2015
DOI: 10.1002/pbc.25575
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 dosing study of ruxolitinib in children with relapsed or refractory solid tumors, leukemias, or myeloproliferative neoplasms: A Children's Oncology Group phase 1 consortium study (ADVL1011)

Abstract: Background Ruxolitinib, an orally bioavailable JAK1/JAK2 inhibitor, may treat cancers with CRLF2 and/or JAK pathway mutations. Procedure A phase 1 trial of ruxolitinib was performed to determine the maximum-tolerated or recommended phase 2 dose, dose-limiting toxicities (DLTs), pharmacokinetics (PK), and pharmacodynamics (PD) in children with recurrent/refractory solid tumors (STs). Ruxolitinib was administered twice daily (BID) in 28-day cycles at five dose levels (15, 21, 29, 39, and 50 mg/m2/dose). PK and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 31 publications
2
77
0
Order By: Relevance
“…In the phase 1 and phase 2 clinical trials reported to date, twice-daily doses of 15 to 50 mg/m 2 in children and 25 mg in adults were well tolerated. 44,58,59 These values are equivalent to the twice-daily therapeutic oral dose of 1 mg/kg per mouse used in the present study. Our dose level was high enough to downregulate STAT1 activation in circulating MNCs, correct all the clinical and biological manifestations of HLH, and significantly improve Prf1 2/2 mice survival, although no pharmacological data were collected in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the phase 1 and phase 2 clinical trials reported to date, twice-daily doses of 15 to 50 mg/m 2 in children and 25 mg in adults were well tolerated. 44,58,59 These values are equivalent to the twice-daily therapeutic oral dose of 1 mg/kg per mouse used in the present study. Our dose level was high enough to downregulate STAT1 activation in circulating MNCs, correct all the clinical and biological manifestations of HLH, and significantly improve Prf1 2/2 mice survival, although no pharmacological data were collected in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a higher dose of ruxolitinib may be required for optimal inhibition of JAK-STAT signaling in patients with Ph-like ALL overexpressing CRLF2, as often utilized in pediatric patients with Phlike ALL. 16 JAK inhibition with novel type II JAK inhibitors which stabilizes JAK2 in an inactive conformation have shown to suppress the growth of CRLF2+ B-ALL cells, and could be explored therapeutically.…”
mentioning
confidence: 99%
“…6,7,19 Thus, genomic characterization of Ph-like ALL has significant therapeutic implications with the emerging use of kinase inhibitors in this patient population. 6,7,16,[20][21][22][23] Therefore, it is imperative to establish the incidence and clinical/genomic features of Ph-like ALL in adults. Here, we report the genomic characteristics and outcomes of adult patients with Ph-like ALL uniformly treated with a hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone (hyper-CVAD) or an augmented BerlinFrankfurt-Münster (BFM) regimen at a single institution.…”
Section: Introductionmentioning
confidence: 99%